B Cells Control Mucosal-Associated Invariant T Cell Responses to Salmonella enterica Serovar Typhi Infection Through the CD85j HLA-G Receptor - Salerno-Gonçalves, Rosângela; Rezwan, Tasmia; Luo, David; Tettelin, Hervé; Sztein, Marcelo B. (Frontiers in Immunology, 2021)
Mucosal-associated invariant T (MAIT) cells are an innate-like population of T cells that display a TCR Vα7.2+ CD161+ phenotype and are restricted by the nonclassical MHC-related molecule 1 (MR1). Although B cells control MAIT cell development and function, little is known about the mechanisms underlying their interaction(s). Here, we report, for the first time, that during Salmonella enterica serovar Typhi (S. Typhi) infection, HLA-G expression on B cells downregulates IFN- production by MAIT cells. In contrast, blocking HLA-G expression on S. Typhi-infected B cells increases IFN- production by MAIT cells. After interacting with MAIT cells, kinetic studies show that B cells upregulate HLA-G expression and downregulate the inhibitory HLA-G receptor CD85j resulting in loss of MAIT cells. These results provide a new role for HLA-G as a negative feedback loop by which B cells control MAIT cell responses to antigens.